(untitled) (Research, Society and Development, 2021)
Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyneuropathy, also determined as acute idiopathic polyradiculoneuropathy, given by an acquired autoimmune disorder. This syndrome is marked by the loss of the myelin sheath and tendon reflexes, encompassing acute immunomediated polyneuropathies, which can be subdivided into two types: demyelinating and axonal, which can be triggered by an immune trigger due to viral, bacterial, fungal etiology. or genetics. When it comes to GBS by etiology by SARS-COV-2, there are reports in the literature of affected patients who developed neurological manifestations in the post-COVID-19 syndrome, determined by the presentation of symptoms for more than three months after the acute phase of the disease. In this sense, this article aims to describe the main clinical manifestations, diagnosis and treatment for patients affected by GBS in the post-COVID-19 syndrome. A retrospective, bibliographic review was carried out in the MEDLINE / PubMed and LILACS databases, using the descriptors / keywords and Boolean operator: "Coronavirus Infections" AND "Guillain-Barré Syndrome". 86 articles were located and after applying the inclusion and exclusion criteria, eight case report articles were included for analysis. The sex most affected was male (75%), with a mean age of 52 years with a minimum of 21 years and a maximum of 66 years. The presentation symptoms for COVID-19 ranged from asymptomatic (12.5%) to symptomatic (87.5%) with the presence of cough (75%), fever (62.5%) and others. The first neurological manifestation after COVID-19 was in 13 days, with the main neurological manifestations being bilateral peripheral facial paralysis, dysarthria and areflexia. When analyzing the cerebrospinal fluid, there was the presence of albuminocytological dissociations (87.5%) and olioclonal bands (12.8%). When electroneuromyography was performed, the neurophysiological subtypes found were classified mostly by demyelinating neuropathy (50%), with its main variant for GBS for classical motor sensitivism (62.5%). Most patients, after diagnosis of the main variant for GBS (87.5%), were treated with intravenous immunoglobulin (75%) and plasmapheresis (12.5%), with favorable clinical evolution and later hospital discharge.